Micro Teaching Online selama Wabah COVID-19: Studi pada mahasiswa Jurusan Bahasa Inggris Universitas Islam Negeri Semarang - M. Firdaus Annur; Putroe Ilmia; Siti Tarwiyah (Academy of Education Journal, 2026)
This study explores the online micro-teaching process through e-learning during the COVID-19 pandemic and identifies challenges faced by students. Using a descriptive qualitative approach, data were collected through observation and interviews, then analyzed through data collection, reduction, presentation, and conclusion drawing. The study involved English Education students taking a micro-teaching course at UIN Walisongo Semarang. Findings reveal seven key stages in micro-teaching: lesson plan preparation, training in eight fundamental teaching skills (questioning, reinforcement, variation, explanation, lesson opening & closing, small group discussion guidance, classroom management, and small-group/individual teaching), planning and applying these skills, competency assessment, learning module development, and creating tutorial videos for online teaching. However, students encountered several obstacles, including unstable internet access, limited data quotas, unclear lecturer feedback, technical difficulties in video recording, and poor time management. These challenges highlight the need for effective strategies to improve the efficiency of online micro-teaching.